Developing Talent Not Privilege: An Exploration of the Vulnerable-Resilient Vessel within the Everyday ‘Student Journey’ at an English Arts University - Hayward, Beverely (International Journal for Talent Development and Creativity, 2023)
To celebrate the 10th anniversary of the International Journal of Talent Development and Creativity, I return to the vision of the publication, by understanding what it means to develop talent and creativity in the 21st century. This paper celebrates the development of talent in the context of an arts education for neurodiverse students. Often talent is overlooked in pedagogies of neoliberalism, as the ethos for universities favour the market forces of competition and survival. In particular, post-1992 universities, face fierce competition for students due to market saturation. Students’ needs have been forgotten in unethical recruitment practices that are disguised as increased access. Unfortunately, it is to the detriment of welfarism and what bell hooks terms ‘the care of the soul’. This paper partly explores the current milieu, at university to contextualise the tenacity, resilience and vulnerability of those working and learning. Here talent and development are encouraged in young people, who have hitherto been marginalised and disadvantaged. It celebrates the successes, facilitated in part by the mediation of a small team of study skills support workers, including the author. Accordingly, a feminist approach engages auto-ethnography, and psychosocial spaces of the imaginary. Borrowing from the oeuvre of Feminism, Adult Education and Creative Possibility: Imaginative Responses, woven within the threads of this theory are small vignettes, art and poetry by one study skills support worker and the author. Speaking from the lived experience of being a child from a working-class background who is neurodiverse, I understand what it means to be marginalised in the English system of education. From the experiences of the support worker and me, this paper explores the ‘student journey’ within the context of inclusion in higher education, followed by an exploration of creative practices and reflections.